2014
DOI: 10.7314/apjcp.2014.15.3.1119
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Anomalies, Chromosomal Aberrations and Proliferation Rates in Cultured Lymphocytes of Head and Neck Cancer Patients

Abstract: Head and neck cancers (HNC) are extremely complex disease types and it is likely that chromosomal instability is involved in the genetic mechanisms of its genesis. However, there is little information regarding the background levels of chromosome instability in these patients. In this pilot study, we examined spontaneous chromosome instability in short-term lymphocyte cultures (72 hours) from 72 study subjects -36 newly diagnosed HNC squamous cell carcinoma patients and 36 healthy ethnic controls. We estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Also the metabolic syndromes like obesity and hypertension are the leading possible factors for renal cell carcinoma which are linked to diabetes mellitus (Satrudhan et al, 2012). Also studies has shown oxidative stress correlated with DNA damage (Cinkilic et al, 2009) in T2DM and T1DM patients and an increase in genomic instability in precancerous patients (George et al, 2014). Thus oxidative damage over time may cause genomic instability and may lead to cancers.…”
Section: Introductionmentioning
confidence: 97%
“…Also the metabolic syndromes like obesity and hypertension are the leading possible factors for renal cell carcinoma which are linked to diabetes mellitus (Satrudhan et al, 2012). Also studies has shown oxidative stress correlated with DNA damage (Cinkilic et al, 2009) in T2DM and T1DM patients and an increase in genomic instability in precancerous patients (George et al, 2014). Thus oxidative damage over time may cause genomic instability and may lead to cancers.…”
Section: Introductionmentioning
confidence: 97%
“…An increased MN frequency in the circulating lymphocytes indicates increased cancer risk for those exposed to genotoxic agents (Znaor et al, 2003;Bonassi et al, 2007;. The CBMN assay is increasingly used these days to assess the cancer risk associated to genotoxic exposures (El-Zein et al, 2011) and genomic instability of several diseases (Wu et al, 2012;Abdullah and Orta, 2012;Wang et al, 2013;Sitaraman et al, 2014;George et al, 2014;Soares et al, 2014;Main et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…NA analysis complements MN analysis, so these were observed in tandem with MNs. In buccal cells we looked for the presence of bridges, constrictions, elongated nuclei, kidney-shaped nuclei, notched, lobed nuclei, binucleated, in prophase and apoptotic cells while in lymphocytes we looked for the presence of bridges, buds, tails, dumbbell-shaped nuclei, irregularly shaped, fused, horseshoe-shaped, circular-shaped, binucleated, apoptotic cells and necrotic cells (Torrez-Bugarín and Ramos-Ibarra 2013; George et al 2014;Fenech et al 2016;Kravtsov et al 2017;Nersesyan et al 2022). The frequency of nuclear abnormalities (NA%) for each cell type was calculated with the following formula (Drumond et al 2012):…”
Section: -Blood Samplesmentioning
confidence: 99%